2023
DOI: 10.3389/fimmu.2023.1227833
|View full text |Cite
|
Sign up to set email alerts
|

Application of toll-like receptors (TLRs) and their agonists in cancer vaccines and immunotherapy

Samik Chakraborty,
Juan Ye,
Herui Wang
et al.

Abstract: Toll-like receptors (TLRs) are pattern recognition receptors (PRRs) expressed in various immune cell types and perform multiple purposes and duties involved in the induction of innate and adaptive immunity. Their capability to propagate immunity makes them attractive targets for the expansion of numerous immunotherapeutic approaches targeting cancer. These immunotherapeutic strategies include using TLR ligands/agonists as monotherapy or combined therapeutic strategies. Several TLR agonists have demonstrated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 221 publications
(410 reference statements)
0
2
0
Order By: Relevance
“…The situation in vivo is however far more complex. TLR agonists have been tested as adjuvants to increase the efficacy of cancer vaccines or cancer treatment ( 54 ). In MM, it was shown that a TLR9 agonist could restore the ability of patient-derived plasmacytoid dendritic cells (pDCs) to stimulate T-cell proliferation and that activating TLR9 in a xenograft MM model reduced tumor load ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The situation in vivo is however far more complex. TLR agonists have been tested as adjuvants to increase the efficacy of cancer vaccines or cancer treatment ( 54 ). In MM, it was shown that a TLR9 agonist could restore the ability of patient-derived plasmacytoid dendritic cells (pDCs) to stimulate T-cell proliferation and that activating TLR9 in a xenograft MM model reduced tumor load ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various immunomodulatory agents, such as toll-like receptor agonists, cytokines, and immune cell modulators, are being investigated in CRC to enhance anti-tumor immune responses [ 191 , 192 ]. These agents may target pathways affected by TC-mediated immunomodulation, promoting a more favorable immune microenvironment for anti-tumor activity.…”
Section: Tuft-cell-based Crc Therapies and Their Considerationsmentioning
confidence: 99%
“…This is supported by several ongoing clinical trials assessing the efficacy of combining TLR agonists with chemotherapy, radiotherapy, or various other immunotherapies, also in the context of HPV-associated cancers. [176][177][178] Lastly, their efficacy suggests they could serve as adjuvants for the production of therapeutic HPV vaccines aimed at promoting cellular responses while disrupting the anti-inflammatory microenvironment generated by HPV + cells. 179…”
Section: Tlr Agonistsmentioning
confidence: 99%